2013
DOI: 10.2971/jeos.2013.13055
|View full text |Cite
|
Sign up to set email alerts
|

Signal of single scattering albedo in water leaving polarization

Abstract: The purpose of this article is to examine whether the change in single scattering albedo in the surface layer of the sea will cause significant changes in the polarization of light emerging from the sea. The results of a polarization resolving Monte Carlo radiative transfer calculations are presented. Bubble clouds of different bubble concentrations are used to achieve a wide range of single scattering albedo variability. The variability of the polarization signal is largest in the direction looking towards th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 25 publications
(26 reference statements)
2
8
0
Order By: Relevance
“…Moreover, polarization may be used to separate the inorganic and biogenic parts of suspended matter (see Gilerson et al [8], Chami [9] and Tonizzo et al [10]). It has been shown by Piskozub and Freda [11], that degree of polarization over sea surface strongly depends on single scattering albedo changes caused by various concentrations of bubbles. It is also well known that reflected light is partly polarized, that is why polarization can significantly improve the quality of signal coming from below surface when measured above the seawater.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, polarization may be used to separate the inorganic and biogenic parts of suspended matter (see Gilerson et al [8], Chami [9] and Tonizzo et al [10]). It has been shown by Piskozub and Freda [11], that degree of polarization over sea surface strongly depends on single scattering albedo changes caused by various concentrations of bubbles. It is also well known that reflected light is partly polarized, that is why polarization can significantly improve the quality of signal coming from below surface when measured above the seawater.…”
Section: Introductionmentioning
confidence: 99%
“…CC BY 4.0 License. ongoing numerical radiative transfer models, very few of them include light polarization (Piskozub and Freda, 2013;Chami et al, 2001). Most current methods of radiative transfer treat light as a scalar to hasten the computations.…”
mentioning
confidence: 99%
“…Their analysis revealed that the application of the polarization of light in ocean color algorithms might significantly improve the retrieval of hydrosol properties, especially in coastal waters. Piskozub and Freda (2013) applied their polarized radiative transfer model to the Baltic Sea. They examined how scattering properties of seawater represented by a single scattering albedo affected the polarization of water-leaving radiance.…”
mentioning
confidence: 99%
“…Scattering properties of seawater represented by single scattering albedo that affects the polarization of water-leaving radiance was examined by Piskozub and Freda (2013). They used bubble layers of various concentration to simulate its impact 35 2 Ocean Sci.…”
mentioning
confidence: 99%
“…A simulation has been made with Monte Carlo algorithm created by Jacek Piskozub and described in Piskozub and Freda (2013). This version of algorithm not only collects information about various events, in which virtual photons are involved, like reflection, refraction, scattering, absorption or leaving the atmosphere.…”
mentioning
confidence: 99%